Differences in the Performance and Phosphorus-Use Efficiency of Some Tropical Rice (Oryza sativa L.) Varieties - Akinrinde, E.A.; Gaizer, T. (Pakistan Journal of Nutrition, 2006)
Deficiency of phosphorus (P) is widespread in tropical and temperate acid soils. Six rice ( Oryza sativa L) varieties (TOX 4008 – 34, TOX 3499-84, FARO 51, LOCAL CHECK, FAROX 317, and WAT 107 – TGR) were evaluated for their P nutrition capability at 0, 50, 100, 150 and 200 mg kg -1 levels of P applied in an Alfisol. Plant height (from 3 weeks after planting, WAP), number of tillers (from 4 WAP), as well as dry matter (DM) yields, P concentration and uptake in partitioned plant parts and P - use efficiency parameters were estimated after 6 weeks of growth. Plant height at 4 WAP, content and uptake of P determined in shoot and root were significantly (P < 0.01) influenced by P application rates. The varieties also differed significantly in their growth; DM production and P - use efficiency, thus permitting their categorization into efficient or non-efficient and responsive or non-responsive types.